INIBAP technical guides 1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Screening of Musa germplasm for resistance and tolerance to nematodes guide number 1, 48 pp. ISBN 2 910 810 16 X